Physical assessment skills practised by critical care nurses: A cross‐sectional study - Rosli, Syeril Nadia; Soh, Kim Lam; Ong, Swee Leong; Abdul Halain, Azura; Abdul Raman, Rosna; Soh, Kim Geok (Wiley-Blackwell Publishing, 2023)
Background: Physical assessment skills are essential to clinical decision-making in nursing as they help nurses to identify and respond to patients' deterioration. Nurses develop confidence and can detect any out-of-range parameters in diagnosing and treating patients. Prior studies surveyed 120 skills but did not explicitly assess critical care. Aim: To determine the range of physical assessment skills practised by critical care nurses and their adoption factors. Study design: This study uses a cross-sectional survey design. A self-administered questionnaire evaluating 40 physical assessment skills was conducted with 133 staff nurses (response rate: 96.4%) in three critical care units at a Malaysian government hospital between November 2019 and January 2020. Results: Most nurses applied 32 (80%) skills during every working shift, involving the vital signs and all body systems except the gastrointestinal system. Five skills (12.5%) were occasionally applied, while three skills (7.5%) were rarely applied or not part of most nurses' clinical practice. About 20% of the nurses did not routinely check the respiration rate. Medical and surgical intensive care unit nurses (U = 1129, p < .001) and nurses who had served over 10 years (H (2) = 9.60, p = .008) used more physical assessment skills than others. Nurses felt that continuing nursing education, participating in relevant courses and implementing standardised forms to record physical assessments would improve the application of such skills. Conclusion: Clinical practice in these critical care settings challenges the assertion that physical assessment is vital to critical care nursing roles. Concerns highlighted by the nurses should be addressed by nursing management so that the application of physical assessment skills can be enhanced, especially in critical care settings. Relevance to Clinical Practice: The findings indicated that physical assessment skills in critical care need to be improved. Education and training should emphasise these skills.